2016
DOI: 10.1159/000448992
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Executive Changes in Drivers with Parkinson's Disease: Study Using Neuropsychological and Driving Simulator Tasks

Abstract: Background/Aims: (1) To investigate how specific executive functions change over 2 years in drivers with Parkinson's disease (PD) compared to controls, using both neuropsychological and driving simulator tasks; and (2) to explore the association between the decline of specific executive functions and changes in driving habits in PD. Methods: Sixteen PD patients and 21 controls underwent neuropsychological testing twice and performed tasks on a driving simulator, with an interval of approximately 2 years. Quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
1
3
0
6
Order By: Relevance
“…In addition to worsening of global cognition, deterioration of error counts was predicted by poor baseline visual sensory function (near visual acuity) and worsening of visual processing speed and attention, visual working memory, cognitive flexibility and set shifting, and ADL score. These predictors are consistent with the most frequent nonmotor deficits in mild to moderate PD, and reflect impairments in primary neural demands of driving (visual function across all levels and executive functions 25 ). The UPDRS-ADL score, but not the UPDRS motor score, was also an important predictor of driving cessation in our cohort, 8 suggesting a measure of function over a period of time, rather than a snapshot of severity of parkinsonism, is a better metric of decline of driving safety over time.…”
Section: Depression Geriatric Depression Scale Was Usedsupporting
confidence: 67%
“…In addition to worsening of global cognition, deterioration of error counts was predicted by poor baseline visual sensory function (near visual acuity) and worsening of visual processing speed and attention, visual working memory, cognitive flexibility and set shifting, and ADL score. These predictors are consistent with the most frequent nonmotor deficits in mild to moderate PD, and reflect impairments in primary neural demands of driving (visual function across all levels and executive functions 25 ). The UPDRS-ADL score, but not the UPDRS motor score, was also an important predictor of driving cessation in our cohort, 8 suggesting a measure of function over a period of time, rather than a snapshot of severity of parkinsonism, is a better metric of decline of driving safety over time.…”
Section: Depression Geriatric Depression Scale Was Usedsupporting
confidence: 67%
“…A number of studies have incorporated cognitive assessments in an attempt to determine which test performances are associated with the driving competence of patients with PD. Most studies reported an association between cognitive functioning and driving competence [ 3 , 12 , 26 28 , 31 , 32 , 36 , 38 40 , 43 , 46 , 48 52 ]. However, some studies also reported no associations between cognition and driving in PD patients [ 1 , 33 , 53 ], so results are inconsistent.…”
Section: Resultsmentioning
confidence: 99%
“…However, some studies also reported no associations between cognition and driving in PD patients [ 1 , 33 , 53 ], so results are inconsistent. Driving errors were particularly associated with lower performances in cognitive flexibility [ 26 , 27 , 38 , 39 , 49 , 52 ], visuoconstructional abilities [ 26 , 36 , 39 ], attention [ 12 , 27 , 32 , 36 , 40 , 46 ], psychomotor speed [ 46 , 51 ], working memory [ 12 , 49 ], set shifting [ 12 , 48 ], information processing [ 12 , 49 ], contrast sensitivity [ 27 , 31 , 43 , 48 , 51 ], visual scanning [ 32 ], visual acuity [ 32 , 40 ], speed of visual processing [ 3 , 27 , 28 , 40 ], and visual memory [ 3 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nicht motorische Symptome der Parkinsonkrankheit können bereits Jahre vor den motorischen Symptomen einsetzen [11,12] und mit steigender Krankheitsdauer zunehmen [13,14]. Schlechtere Leistungen in Aufmerksamkeit, der Aufnahme und Verarbeitung visueller sowie visuell-räumlicher Informationen und in Teilbereichen exekutiver Funktionen sind bei Parkinson-Patienten mit mehr Fahrfehlern und Veränderungen im Fahrverhalten assoziiert [5,9,[15][16][17]. Zusätzliche Aufgaben, z.…”
Section: Motorische Kognitive Und Visuelle Parkinsonsymptome Und Fahrkompetenzunclassified
“…Zusätzliche Aufgaben, z. B. visuelles Suchen, können zu einer kognitiven Überlastung [16,18] und zu einem erhöhten Unfallrisiko führen [19]. Betrachtet man die Demenzerkrankung, ist besonders bei mittleren-schweren Ausprägungen die Fahrkompetenz beeinträchtigt [20].…”
Section: Motorische Kognitive Und Visuelle Parkinsonsymptome Und Fahrkompetenzunclassified